Effect of Some Ameliorants on Chemical Properties Of Toba Highland Peat and Growth of Rice (Oryza sativa L.) - Berkat Julianto Banjarnahor; Sarifuddin Sarifuddin; Kemala Sari Lubis (Jurnal Agroekoteknologi, 2018)
ABSTRACT The aim of this study to know effect of some ameliorants by toba plateau peat’s chemical characteristic for growth and production Ciherang. The study was conducted at greenhouse of Faculty of Agriculture, University of Sumatera Utara and analysed at PT.Socfin Indonesia and Laboratories Research and Technology. This research used randomized block design non factorial with eight treatments there were G0 (control), G1 (volcanic ash 250 g / pot), G2 steel slag 50 g / pot), G3 (seawater 250 ml / pot), G4 (volcanic ash 250 g + steel slag 50 g / pot), G5 (volcanic ash 250 g + seawater 250 ml / pot), G6 (steel slag 50 g + seawater 250 ml / pot), G7 (volcanic ash 250 g + steel slag 50 g + sea water 250 ml / pot) with three replications. The results showed ameliorant steel slag 50 g increased the soil up to pH 4:35, combinations volcanic ash 250 g and the steel slag 50 g increased the electrical conductivity up to 0,194 mmhos/cm and combination of volcanic ash 250 g and the 50 g of steel slag increased rice growth there are toba highland peat 107,3 cm in height, 25 clumps in number of vegetatif and generatif tillers and reduce the percentage of empty grain up to 78.73%, %, and aplication combination ameliorant volcanic ash 250 g with 50 g of steel slag as well as sea water 250 ml increase the production of rice plants / pots and grain weight 1000 grain with the value of each 24.12 grams and 21.47 grams Top of Form   Keywords: Highland Toba peat, Rice Ciherang variety, Seawater, Steel slag, Volcanic ash